A Study of Courageous Leadership of Mohterma Benazir Bhutto from 1952 to 2007 - Dr. Aijaz Ali Khoso (International Research Journal of Education and Innovation, 2020)
Mohterma Benazir Bhutto was a great leader. She contributed in restoration of democratic process and sustainable development policies for our homeland. She was first woman prime minister of Pakistan, very popular in Asian as well as Western societies. No any woman in Pakistan has achieved the global status like Benazir Bhutto. Her leadership style is a vibrant role for women and men leaders equally. The books, newspapers, and stories are published regarding her life span, political contributions. The text-books stuff is not published regarding her political struggle which is urgently needed for the present generations to learn about effective leadership trends, and genuinely strive for the future of Pakistan. The series of events during her Government period, collection of her speeches, innovative initiatives of her policies and plans are eye opening for women and men alike. The present research paper is an intellectual contribution on political and social dynamism and her contributions from her birth (1953) to martyrdom December (2007).